The epidemiology of Lassa fever in Ghana: a study on the 2023 Lassa fever outbreak in Ghana - Kwasi Atweri Akowuah; Magdalene Sarah Ofori; Deborah Pratt; Abigail Abankwa; Evelyn Yayra Bonney; Nancy Enimil; Eric Odei; Theodore Worlanyo Asigbee; Dennis Laryea; Prince Ketorwoley; Juliana Naa Dedei Acquah Amaning; Maame Serwaa Boapea; et al. (Frontiers in Public Health)
BackgroundViral disease outbreak remains a key public health concern given its impact on life and livelihood. Historical data suggests Lassa fever is endemic in several West African countries with sporadic cases occurring elsewhere in the region. In February 2023, Ghana recorded its second outbreak of Lassa fever following that of 2011. The present study sought to document the epidemiology of the recent outbreak in Ghana.MethodsThe study used data from the case investigation forms accompanying samples submitted to Noguchi Memorial Institute for Medical Research between February and March 2023 for Lassa fever testing. Descriptive analysis was used to analyse and report the demographic characteristics. Inferential statistics was used to determine associations between the study variables.ResultsThe overall positivity rate was 5.19% out of the 539 samples received. Most cases were confirmed in the Month of February. Positivity rate was higher among females (5.65%). Over 90% of all confirmed cases were from the Greater Accra Region. Case burden for LF was highest among healthcare professionals and also adults aged 25–35 years. The commonly reported symptoms among confirmed cases included headache, intense fatigue, fever, and muscle/joint pain.ConclusionLassa fever was confirmed among 5.19% of the suspected cases. Transmission was largely through contact with the highest burden among healthcare workers which is suggestive of poor infection control procedures. There is a need to build and sustain fundamental public health capacities to recognise, diagnose, report, and respond to risks of public health concern and interest.